ANALISIS KINERJA PELAYANAN APOTEK DAN KINERJA KEUANGAN PADA APOTEK PROGRAM RUJUK BALIK (PRB)-KRONIS BPJS DAN APOTEK TIDAK BEKERJA SAMA BPJS DI KOTA BOGOR, JAWABARAT - M. Kenli Kendi Tampoliu; MGS. Aritonang; Yusi Anggriani (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2020)
The number of JKN participants increase continuously everyday. Therefore, health facilities should be grow and developed well to serve them. One of the facility is pharmacy. In Bogor, there are three districts that do not have BRP pharmacy, they are East Bogor, North Bogor and Tanah Sareal. The less and uneven of pharmacy on those districts will affect the eviciency and accesibility of the participants. We could say that the accesibility is not good on those districts. And if it does, it will affect the satisfaction of patients against the BRP. This research was conducted in Bogor City. The purpose of this research is to find out the comparison of service performance and financial performance between BRP-Chronic pharmacy cooperating to BPJS and pharmacy non cooperating to BPJS. This research was conducted by using descriptive comparative method with qualitative and quantitative approach. It was build with survey, questionaire, observation and interview. Using purposing sampling, there was 2 BRP-Chronic pharmacies and 10 non BRP-Chronic pharmacies that become the sample of this research. The instruments were developed based on Permenkes number 73 on 2016. The qualitative data analysis method was made descriptively. The qualitative data was presented descriptively to explain the qualitative data. The result of this research showed that the BPR-Chronic pharmacies were more prime on pharmaceutical preparations, clinical pharmaceutical service, pharmaceutical service quality evaluation, and ensuring the availability. On the other hand, non cooperating to BPJS pharmacies were more excellent on pharmaceutical resources and service report. The result of financial performance research showed that pharmacy non cooperating to BPJS was better than BRP-Chronic. The BRP-Chronic has problem on claiming, not being collected and late claim payment. Pharmacy non cooperating to BPJS was rely on clients’ prescriptions and suplement salling and also it use the new technology such as media social and e-commerce.